(untitled) (Revista de História Regional, 2009)
This work’s subject matter is the slavery’s riots. It’s goal may be not be taken as the studies about riot’s significance. First of all, this work shows some connections between the tries to lay restraints on São Paulo entrance slavery and slave-holder murders. Second of all, this work shows other connections between the Abolition and the Brazil Empire political system as a proposition for history debate concerning to the Abolition and the slavery’s riots.